Cannabinoids: a review on neurobiological and neuropsychopharmacological bases of dependence and rewarding effects - Alıcı, Tevfik; Uzbay, İ. Tayfun (Journal of Dependence, 2006)
Cannabinoids have been associated with a wide range of pharmacological effects, some of which have potential therapeutic benefit while others result in negative outcomes, such as abuse and dependence. Cannabis is the most commonly used illicit substance in the world, but only recently reliable preclinical models have become available for investigating the rewarding and addictive properties of its primary psychoactive constituent, Δ9-tetrahydrocannabinol (Δ9-THC). Starting with the discovery of an endogenous brain cannabinoid system with specific receptors and their endogenous ligands, and through the use of the tools such as specific CB1 receptor antagonist, SR141716A, and various transgenic models, considerable advances have been made in understanding the mechanisms underlying cannabinoid dependence. The objective of this review is to evaluate the results of various animal models, such as drug-discrimination, conditioned place preference, self-administration, and precipitated withdrawal, currently in use to facilitate our understanding of the rewarding and addictive properties of cannabinoids, and of the neurobiological mechanisms that may underlie these properties.